The extent of the use of Business Processes Reengineering entrance in the reform of basic education departments A field study in the first episode schools in Tartous (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aimed to identify the extent of the use of Business processes reengineering entrance in the reform of basic education department in the first episode schools in Tartous, as well as to identify The differences between the views of respondents about extent at the use of business processes reengineering entrance in the reform of the education departments depending on the following variables (sex, scientific and educational qualification, years of experiences,and job Title). The research used Descriptive analytical method, The sample included (276) Administrative and teachers for the academic year 2016/2017. The Questionnaire consisted of (52) items. The research' conclusions are: degree of The use of entrance of business processes reengineering came moderate with a mean (1,88) and relative weight (62,67%) The result also showed no statistically significant differences between the responses of the respondents attributes to the (sex, and years of experiences), While there were statistically significant differences due to the Variables (Qualification, and Job Title). The research has offered several proposals including, for further research and studies related to reengineering of administrative processes so that addressed and number of the dimensions that are not addressed in this study such as: The use of technology and information systems.